La vía mística en Villoro - Ferreira González, Jesús Emmanuel (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
The following investigation approaches topics of the work of Villoro very little treaties, but not hence of little importance. He/she helps us to have a deeper vision of their work and to repensar the philosophy in general. They are collateral topics to the main lines philosophical of our Mexican thinker that keep certain lateralidad in the sense of that the main topics of their work have been about the indigenismo, problems of the one multiculturalism and interculturalidad, Marxism, phenomenology, epistemology, politics and ethics. The topics that here are approached they are on mystic, aesthetics, history philosophy, philosophy of the religion, utopia, Hindu thought, reflections on the sense and the one I silence that in spite of their irrational character, like they are commonly conceived, they are marked by a strict, logical and systematic rationalism; they have a logical character- rational that always looks from the lens epistemological to all the angles of the world of that lived that he/she settles down between the man and the being in general. These thematic ones are very far from the abstract and universal philosophy, but they are very important in the mark of a theory of the culture and of an anthropological ethics, that is to say, in the relationship of him human and their world of significances; in the vital dimension of the culture where the one man looks for the sense of the existence, it is where they charge his importance; they belong to the sphere of the practical reason.

La siguiente investigación aborda temas de la obra de Villoro muy poco tratados, pero no por ello de poca importancia. Nos ayuda a tener una visión más profunda de su obra y a repensar la filosofía en general. Son temas colaterales a las principales líneas filosóficas de nuestro pensador mexicano que guardan cierta lateralidad en el sentido de que los temas principales de su obra han sido acerca del indigenismo, problemas del multiculturalismo e interculturalidad, marxismo, fenomenología, epistemología, política y ética. Los temas que aquí se abordan son sobre mística, estética, filosofía de historia, filosofía de la religión, utopía, pensamiento hindú, reflexiones sobre el sentido y el silencio, que a pesar de su carácter irracional, como se conciben comúnmente, están marcados por un racionalismo estricto, lógico y sistemático; tienen un carácter lógico- racional que siempre mira desde el lente epistemológico a todos los ángulos del mundo de lo vivido que se establece entre el hombre y el ser en general. Estas temáticas son muy alejadas de la filosofía abstracta y universal, pero son muy importantes en el marco de una teoría de la cultura y de una ética antropológica, es decir, en la relación de lo humano y su mundo de significaciones; en la dimensión vital de la cultura, en donde el hombre busca el sentido de la existencia, es donde cobran su importancia; pertenecen a la esfera de la razón práctica.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2008-0014; Multiculturalismo; Interculturalidad; Marxismo; Utopía; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/46